2016
DOI: 10.1039/c6ee01046f
|View full text |Cite
|
Sign up to set email alerts
|

An efficient bifunctional two-component catalyst for oxygen reduction and oxygen evolution in reversible fuel cells, electrolyzers and rechargeable air electrodes

Abstract: We report on a non-precious, two-phase bifunctional oxygen reduction and evolution (ORR and OER) electrocatalyst with previously unachieved combined roundtrip catalytic reactivity and stability for use in oxygen electrodes of unitized reversible fuel cell/electrolyzers or rechargeable metal-air batteries. The combined OER and ORR overpotential, total, at 10 mA cm À2 was a record low value of 0.747 V. Rotating Ring Disk Electrode (RRDE) measurements revealed a high faradaic selectivity for the 4 electron pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
169
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(170 citation statements)
references
References 49 publications
1
169
0
Order By: Relevance
“…This phenomenon, also known as "house of cards" structure, was widely proposed in 2D nanosheets with distinguished electrical property between laminates and edges. [34] Therefore, the array-like Ni 2 Co I-II Fe-LDH/N-GO can be beneficial to the gas evolution reaction of OER process [11] and gas consumption reaction like ORR process. The morphologies in Figure 2c,d confirmed that Ni 2 Co III Fe-LDH/N-GO was in analogy to nanoarray material, where N-GO behaved as substrate and the vertically grown Ni 2 Co III Fe-LDH played the crucial role in electrocatalysis.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon, also known as "house of cards" structure, was widely proposed in 2D nanosheets with distinguished electrical property between laminates and edges. [34] Therefore, the array-like Ni 2 Co I-II Fe-LDH/N-GO can be beneficial to the gas evolution reaction of OER process [11] and gas consumption reaction like ORR process. The morphologies in Figure 2c,d confirmed that Ni 2 Co III Fe-LDH/N-GO was in analogy to nanoarray material, where N-GO behaved as substrate and the vertically grown Ni 2 Co III Fe-LDH played the crucial role in electrocatalysis.…”
Section: Resultsmentioning
confidence: 99%
“…The Tafel analysis depicted in Figure a reveals a slope of 60–62 mV/dec, indicating a good control over O 2 mass transport and excluding possible artefacts often observed in thick film electrodes . Very interesting results have been reported for Fe‐based electrocatalysts based on either bulk or electrodeposited Fe obtained by pyrolysis of appropriate iron precursors or solvothermal approaches also using different C‐based supports, and for mixtures of Fe and other transition metals . However, such a high activity displayed by an iron‐based catalyst Fe(np)/nCs is unprecedented.…”
Section: Methodsmentioning
confidence: 90%
“…[16,51,58,[64][65][66][67][68] This method requires a certain temperature to start the hydrolysis process and is performed in autoclaves. Urea, dimethylformamide (DMF) and hexamethylenetetramine (HMT) are typical hydrolysis agents used.…”
Section: Homogeneous Precipitationmentioning
confidence: 99%